Still radical after all these years: George Kelly's The psychology of personal constructs. (April 2013) - Winter, David A
George Kelly's The psychology of personal constructs put forward a new psychology that viewed people as actively constructing and anticipating their worlds. This paper considers personal construct theory and its philosophy; personal construct assessment techniques; the personal construct view of psychological disorder and its treatment; and the wide range of other applications of personal construct theory. It is concluded that personal construct psychology remains a radical approach over half a century after Kelly published his magnum opus.